Aged Garlic Extract (AGE) and Its Constituent S-Allyl-Cysteine (SAC) Inhibit the Expression of Pro-Inflammatory Genes Induced in Bronchial Epithelial IB3-1 Cells by Exposure to the SARS-CoV-2 Spike Protein and the BNT162b2 Vaccine - Jessica Gasparello; Chiara Papi; Giovanni Marzaro; Alberto Macone; Matteo Zurlo; Alessia Finotti; Enzo Agostinelli; Roberto Gambari (Molecules)
Garlic (Allium sativum L.) is a species of the onion family (Alliaceae) widely used as a food and a folk medicine. The objective of this study was to determine the effects of AGE (aged garlic extract) on pro-inflammatory genes relevant to COVID-19. To this aim, we treated bronchial epithelial IB3-1 cells with SARS-CoV-2 spike protein (S-protein) or with the COVID-19 BNT162b2 vaccine in the absence or in the presence of AGE. The results obtained demonstrated that AGE is a potent inhibitor of the S-protein-induced expression of the IL-1β, IL-6 and IL-8 genes. Bio-Plex analysis demonstrated that AGE reduced release of IL-6 and IL-8, which were highly induced by S-protein. No inhibition of cells’ growth, toxicity and pro-apoptotic effects were found in AGE-treated cells. The effects of one of the major AGE constituents (S-allyl cysteine, SAC) were studied on the same experimental model systems. SAC was able to inhibit the S-protein-induced expression of IL-1β, IL-6 and IL-8 genes and extracellular release of IL-6 and IL-8, confirming that S-allyl-cysteine is one of the constituents of AGE that is responsible for inhibiting S-protein-induced pro-inflammatory genes. Docking experiments suggest that a possible mechanism of action of SAC is an interference with the activity of Toll-like receptors (TLRs), particularly TLR4, thereby inhibiting NF-κB- and NF-κB-regulated genes, such as IL-1β, IL-6 and IL-8 genes. These results suggest that both AGE and SAC deserve further experimental efforts to verify their effects on pro-inflammatory genes in SARS-CoV-2-infected cells.